Maahanmuutto ja työvoiman riittävyys: Taloudellisten vaikutusten arviointia - Juha M. Alho; Aki Kangasharju; Jukka Lassila; Tarmo Valkonen (The Research Institute of the Finnish Economy (ETLA), 2023)
– This Report analyzes the impacts of population ageing on the Finnish economy and the possibilities to avoid its negative effects by increasing net migration. Our calculations show that a yearly net migration of 44,000 persons is needed to stabilize the size of the birth cohorts and the labor force with the current age and gender structure of net migration. The reason for a such high number is the projected low total fertility rate. As a baseline for our economic analysis, we consider future net migration of 15,000 persons, also projected by Statistics Finland. We utilize in our numerical calculations a dynamic general equilibrium model, which provides, e.g., the change in investments induced by the additional migration. The calculations require many assumptions related, for example, to the educational level and the use of social services of the immigrants. This means that the economic results must be considered as approximate. The results indicate that the assumed immigration would have large positive effects on the economic growth and especially on the fiscal sustainability.
Keywords: J11; H68; 330; Migration; Population projection; Economy